2023
DOI: 10.4236/ss.2023.141003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Management and Outcomes of Enterocutaneous Fistulas in Buea Regional Hospital and Laquintinie Hospital of Douala. A Five Years Retrospective Study

Abstract: Background: An Enterocutaneous fistula (ECF) is an abnormal connection between the intestinal tracts or stomach and the skin. They are a major catastrophe to the patient and surgeons and still have a high incidence of morbidity and mortality which varies between 6% -33%; their management remains a big challenge. These patients frequently face complications, and a well-organized multidisciplinary approach must be implemented in their management to improve outcomes. Objectives: Our study aims to assess the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…In our research, we observed that age above 40 years, the presence of small bowel enterocutaneous fistulas (ECF), and lower hemoglobin levels were all identified as statistically significant predictors of unfavorable outcomes. These findings align with previous studies conducted in various regions, including Tanzania [18], India, Nigeria, Iraq, Cameroon, and Guinea [12,20,21,24,[31][32][33][34][35][36][37][38], where similar predictors with addition of comorbidities like HIV and diabetes mellitus were also reported as contributing factors to poor ECF outcomes. It's crucial to remember that small bowel fistulas typically have a high output, which can cause electrolyte imbalances and hypoalbuminemia because of the natural fluid leakage of fistulas and the frequently noticed impaired nutritional status in ECF patients [39].…”
Section: Acknowledgementsupporting
confidence: 91%
See 1 more Smart Citation
“…In our research, we observed that age above 40 years, the presence of small bowel enterocutaneous fistulas (ECF), and lower hemoglobin levels were all identified as statistically significant predictors of unfavorable outcomes. These findings align with previous studies conducted in various regions, including Tanzania [18], India, Nigeria, Iraq, Cameroon, and Guinea [12,20,21,24,[31][32][33][34][35][36][37][38], where similar predictors with addition of comorbidities like HIV and diabetes mellitus were also reported as contributing factors to poor ECF outcomes. It's crucial to remember that small bowel fistulas typically have a high output, which can cause electrolyte imbalances and hypoalbuminemia because of the natural fluid leakage of fistulas and the frequently noticed impaired nutritional status in ECF patients [39].…”
Section: Acknowledgementsupporting
confidence: 91%
“…This phenomenon is not unique to Tanzania, as mortality rates of a similar magnitude have been observed in various other regions. For instance, studies conducted in Cameroon revealed a mortality rate of 38.6% [21], aligning with findings from Muhindo's study in Congo and studies in Nigeria, each reporting mortality rates exceeding 30% and studies conducted in India documented a mortality rate of 29% [19,[21][22][23][24]. These cumulative observations underscore the persistent challenges in managing ECF and the need for concerted efforts to improve patient outcomes across different geographical contexts.…”
Section: Acknowledgementsupporting
confidence: 60%